2015
DOI: 10.1111/dech.12185
|View full text |Cite
|
Sign up to set email alerts
|

Philanthronationalism: Junctures at the Business–Charity Nexus in Post‐war Sri Lanka

Abstract: Over the past few years, the role of private sector organizations as actors and investors in development processes has received increased attention. This article explores the rise of ‘philanthronationalism’ in Sri Lanka: the co‐development of business and philanthropy methods as a response to patronage, nationalization and militarization in the post‐war environment. Drawing on ethnographic research into indigenous forms of corporate social responsibility (CSR), the article identifies four kinds of philanthrona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…That multiple kinds of funders have been observed in other NGO contexts (e.g. see Mueller‐Hirth, ) points to ‘new configurations of market, state and society’, distinct from those associated with less entangled forms of philanthropy (Widger, : 47). The case studies also exemplify how a range of agendas are attracting this funding, suggesting that LGBT advocacy is at a significant juncture in terms of transnational development aid — both more attractive to mainstream donors than in earlier decades when the cause was more controversial, and a site of pushback against perceived foreign encroachments in politically fraught post‐colonial contexts.…”
Section: Discussionmentioning
confidence: 98%
“…That multiple kinds of funders have been observed in other NGO contexts (e.g. see Mueller‐Hirth, ) points to ‘new configurations of market, state and society’, distinct from those associated with less entangled forms of philanthropy (Widger, : 47). The case studies also exemplify how a range of agendas are attracting this funding, suggesting that LGBT advocacy is at a significant juncture in terms of transnational development aid — both more attractive to mainstream donors than in earlier decades when the cause was more controversial, and a site of pushback against perceived foreign encroachments in politically fraught post‐colonial contexts.…”
Section: Discussionmentioning
confidence: 98%
“…Abeysuriya, Mitchell and White (2007) suggest a moral code based on Buddhist values to guide firms in solving sanitation questions via CSR. Widger (2016) identifies four indigenous forms of CSR in Sri Lanka that promote Buddhism as the nation's dominant religion.…”
Section: Macro-normativementioning
confidence: 99%
“…12 Widger has shown that in Sri Lanka, the private sector's philanthrocapitalism is reflecting and shaping dominant Sinhala Buddhist nationalist narratives. 13 Atia has argued that Egyptian faith-based development organisations have linked Islamic charity to forms of self-help such as financial investment and entrepreneurship to produce a 'pious neoliberalism'. 14 Akcali and Korkut's work on Hungary and Turkey demonstrates that the ruling parties, the Hungarian Civic Union (Fidesz) and Justice and Development Party (AKP) have promoted their respective conservative Christian and Islamist politics through urban development projects that entail gentrification and privatisation in a bid for global competitiveness.…”
Section: Introductionmentioning
confidence: 99%